POLISH LANGUAGE IN REZEKNE TODAY. PHONETICS - Kuņicka, Kristīne (Via Latgalica, 2013)
According to Population Census 2011, the estimated number of Poles in Latgale was 20,806 (7%). In the city of Rēzekne there were 795 Poles (2.5%) who constituted the third largest national minority after Latvians and Russians (CSP 2012). The Polish language spoken in Latvia belongs to the Northern-Peripheral Polish (in Polish ‘polszcszyzna północnokresowa’) that functions on the territory of the former Polish-Lithuanian Commonwealth (Ананьева 2004: 103). The aim of the paper is to describe and to analyse the major phonetic peculiarities of the Polish regiolect used by the Poles living in Rēzekne, determining their origin and possible infl uence of Russian and Latvian languages. The author juxtaposes the acquired data with the Standard Polish Language and fi ndings of other researchers considering Peripheral Polish Language. The material for this article has been recorded with a sound recorder at the end of 2011 and at the beginning of 2012 in Rēzekne during structured interviews. The length of the analysed records is 18 hours, which contain speech of thirty informants – three age groups of Poles born from 1932 to 1999 and living in Rēzekne. The data gained during interviews are indicative that since the Second World War there has been a signifi cant decrease in the use of Polish language in all spheres of life. Today the oldest and the middle generation use Peripheral Polish in families and at social events, but the youngest generation learns Standard Polish at school. A very signifi cant and interesting fact is that the representatives of the oldest generation who used and still use the Russian language to communicate with their children (the middle generation born during the Soviet rule), and use Polish when speaking to their grandchildren. After the auditory analysis of the recorded material, the author has selected ten most common and interesting phonetic peculiarities that are characteristic to the speech of Poles in Rēzekne. 1. Considering prosody, in the majority of idiolects the stress falls on the penultimate syllable, which is also characteristic of the Standard Polish, but the stress on ultimate and antepenultimate syllables has also been recorded. 2. The coexistence of the characteristic Standard Polish semi-vowel ṷ and Polish Peripheral dental lateral approximant ł. 3. The use of dental lateral approximant ł instead of the Standard Polish alveolar lateral approximant l. 4. Palatalized pronunciation of alveolar lateral approximant l’ characteristic of Peripheral Polish. 5. Palatalized pronunciation of voiced retroflex affricates č’, ǯ’ instead of the Standard Polish voiced alveolo-palatal ć, ʒ́ , as well as pronunciation of palatalized voiced retroflex č’ instead of the Standard Polish č. 6. Five realisations of “nasal vowels” ǫ, ę: a) synchronous pronunciation ǫ, ę; b) denasalization into o, e; c) asynchronous pronunciation on, on’, en, om, em; d) pronunciation of the sound cluster eŋ with velar nasal consonant ŋ in the ending; e) the realisation of ę with a vowel cluster eu. 7. So called “singing pronunciation” i.e. lengthened pronunciation of vowels in stressed syllables. 8. Merging of unstressed vowels o, e into a. 9. Reduction of unstressed vowel e > i, y. 10. Reduction of unstressed vowel o> u. When describing the Peripheral Polish spoken in the current territory of Lithuania and Belarus, a number of scientists note that various peculiarities of regiolects have emerged under the influence of Russian, Belarusian and Lithuanian languages. The material gathered during the current research allows proposing that phonetic peculiarities of the Polish language used in Rēzekne today are connected with the influence of Russian and Latvian languages. The peculiarities of the oldest generation of speakers were previously recorded by the researcher of Latgalian Polish language Małgorzata Ostrówka, but the current data shows that there are considerable differences in the language of the three studied generations. The main traces of the language spoken by the youngest generation of speakers are palatalized pronunciation of voiced retroflex affricates č’, ǯ’, pronunciation of the Standard Polish semi- vowel ṷ, the use of the dental lateral approximant ł instead of the Standard Polish alveolar lateral approximant l, synchronous realisation of “nasal vowels” ę, ǫ or their realisation with a sound cluster eŋ in the ending. On the contrary, the oldest generation retains dental lateral approximant ł instead of the Standard Polish semi-vowel ṷ, shows traces of “singing pronunciation”, asynchronous and denasalized pronunciation of “nasal vowels”, reduction of unstressed vowels, palatalized pronunciation of alveolar lateral approximant l’, merging of unstressed vowels o, e into a and pronunciation of palatalized voiced retroflex č’ instead of the Standard Polish č. The peculiarities recorded in the speech of the middle generation are a mixture of those of the old and young generations: dental lateral approximant ł and semi- vowel ṷ, various realization of “nasal vowels”, reduction of unstressed vowels, palatalized pronunciation of voiced retroflex č’. Disregarding the fact that the language of the youngest generation is phonetically closer to the Standard Polish language, provisional data gained by the author demonstrate insufficient vocabulary and restricted fluency. The representatives of the oldest and the middle generations are mostly fluent – speak without hesitation. It can be concluded that the Polish language spoken by the Poles in Rēzekne today is an aggregate of idiolects with many common phonetic peculiarities, but their frequency depends on the generation of the speaker and languages s/he uses on everyday basis. Continuation of research on morphology, lexis and syntax of the Polish language spoken in Rēzekne will allow constructing the full picture of the peculiarities of the regiolect.